SELF-DIRECTED LEARNING IN EFL DURING COVID-19 PANDEMIC: AN ANALYSIS OF TEACHER’S PERCEPTIONS AND STUDENTS’ LEARNING AUTONOMY - Wahyudi, Gede Setia; Artini, Luh Putu; Padmadewi, Ni Nyoman (Universitas Pendidikan Ganesha, 2021)
The focus of this research was to analyze the teacher's perception of self-directed learning, to observe activities assigned by the teacher in implementing self-directed learning, and to identify self-directed learning components from the activities assigned by the teacher. The embedded mixed-method was used as a design in which the more dominant was qualitative data rather than quantitative data. SMA Negeri 4 Singaraja was chosen as the research setting and one English teacher who teaches in the tenth-grade at this school was chosen as the subject in this study. The researcher, self-rated questionnaire, observation table, and identification table were used as instruments in this research. The self-rated questionnaire showed that the teacher-rated himself to have high knowledge of self-directed learning but in fact, the observation shows that the teacher was not able to implement well that knowledge into online learning. The data showed the mismatch between teacher perception and activities of self-directed learning assigned to students in online learning.Â